A RFID Tag Antenna for Wearable Application System in Microwave Frequency Band. Issue 1 (July 2021) - Abdullah, N. A. S.; Ramli, N.H.; Yob, R.C
Abstract: A RFID tag antenna for wearable application system in microwave frequency band is proposed and presented. The proposed RFID tag antenna is operated in the microwave frequency band of 1 to 12 GHz. Several numbers of the slot resonator are introduced that attached on jeans fabric as substrate material. The presence of the slot resonator also will be used to generate the unique identification or spectral signature of the RFID tag antenna. In real life, the monostatic radar system, which consists of the Vector Network Analyzer and a horn antenna is configured to test the RFID tag antenna. The performances of the proposed RFID tag antenna are evaluated based on their reflection coefficient, operating frequency, and surface current. The obtained results give a good agreement between the measurements and simulation.